Self-criticism as a mediator between infertility stress and anxious and depressive symptoms in women - Alves, Micaela (2023)
Objective: To explore the mediating role of self-criticism in the relationship between infertility stress and symptoms of anxiety and depression in women diagnosed with an infertility diagnosis or trying to conceive for more than a year. Method: The study included 130 women aged 21 to 44, either diagnosed with infertility or attempting to conceive for over a year, recruited through a non-probabilistic method by self-selection. An online platform was used for the completion of self-report instruments to collect sociodemographic and clinical information and to assess infertility stress, self-criticism, and symptoms of anxiety and depression. Results: Mediational analysis showed that higher levels of infertility stress were associated with more symptoms of anxiety and depression, with this relationship being partially mediated by self-criticism. Conclusions: Infertility, as a stress inducer, can lead to critical internal dialogue, increasing the vulnerability to symptoms of anxiety and depression. Compassion-focused interventions may be beneficial for this population.